Small contact resistance and high-frequency operation of flexible low-voltage inverted coplanar organic transistors - Borchert, James W. (Nat Commun, 2019)
The contact resistance in organic thin-film transistors (TFTs) is the limiting factor in the development of high-frequency organic TFTs. In devices fabricated in the inverted (bottom-gate) device architecture, staggered (top-contact) organic TFTs have usually shown or are predicted to show lower contact resistance than coplanar (bottom-contact) organic TFTs. However, through comparison of organic TFTs with different gate-dielectric thicknesses based on the small-molecule organic semiconductor 2,9-diphenyl-dinaphtho[2,3-b:2’,3’-f]thieno[3,2-b]thiophene, we show the potential for bottom-contact TFTs to have lower contact resistance than top-contact TFTs, provided the gate dielectric is sufficiently thin and an interface layer such as pentafluorobenzenethiol is used to treat the surface of the source and drain contacts. We demonstrate bottom-contact TFTs fabricated on flexible plastic substrates with record-low contact resistance (29 Ωcm), record subthreshold swing (62 mV/decade), and signal-propagation delays in 11-stage unipolar ring oscillators as short as 138 ns per stage, all at operating voltages of about 3 V.